Excessive Maternal Weight and Diabetes Are Risk Factors for Macrosomia: A Cross-Sectional Study of 42,663 Pregnancies in Uruguay - Pereda, Jimena; Bove, Isabel; Pineyro, Maria M. (Frontiers in Endocrinology, 2020)
Objective: To evaluate the risk of macrosomia in newborns from women with gestational diabetes, pregestational diabetes, overweight and obesity in Uruguay in 2012, as well as its association with prolonged pregnancy, maternal age, multiparity and excessive gestational weight gain (EGWG). Methods: We performed a cross-sectional study of 42,663 pregnant women. The risk of macrosomia was studied using logistic regression. Results: Mean maternal age was 26.7 ± 6.8 years. Pregestational overweight and obesity was present in 20.9% and 10.7% of women, respectively. There were 28.1% and 19.8 % of women overweight and obese at the end of the pregnancy, respectively. Furthermore, 0.5% had pregestational diabetes and 8.5% were multiparous. Twenty two percent developed gestational diabetes and 44,9 % had EGWG. The prevalence of macrosomia was 7,9%, significantly more prevalent in males (10% vs. 5.5%, p<0.005). Univariate analysis showed that obesity and overweight pre-pregnancy, obesity and overweight at the end of pregnancy, EGWG, pregestational diabetes, gestational diabetes, multiparity, prolonged pregnancy and male newborn were strongly associated with macrosomia (p<0.0001). Maternal age >35 years did not increase the risk of macrosomia. After multiple logistic regression macrosomia was more likely in pre-gestational obese women (OR 1.24; CI 1.07-1.45), overweight women at the end of pregnancy (OR 1.66; CI 1.46-1.87), obese women at the end of pregnancy (OR 2.21; CI 1.90-2.58), women with EGWG (OR 1.78; CI 1.59-1.98), pregestational diabetes (OR 1.75; CI 1.15-2.69), gestational diabetes (OR 1.39; CI 1.25-1.53), prolonged pregnancy (OR 2.67; CI 2.28-3.12), multiparity (OR 1.24; CI 1.04-1.48) and male newborn (OR 1.89; CI 1.72-2.08). Conclusion: Maternal overweight, obesity, EGWG and gestational diabetes are prevalent in Uruguay, increasing the risk of macrosomia. Efforts to implement strategies to decrease the prevalence of overweight and obesity among women of reproductive age are essential to improve maternal and neonatal outcomes.